Assessment of sea urchin spawning induction and oocyte conservation applied to ecotoxicological assays (Ocean and Coastal Research, 2021)
Marine toxicity tests using sea urchin embryos and larvae are characterized by physicochemical induction for the release of gametes by adult organisms and by the production of excess gamic material after induction. Evaluating the effects of mortality that inducers cause on organisms, and the improvement in oocyte maintenance techniques for subsequent use, are actions of interest in the conservation of species and the sustainable use of this type of biological model. For this study, adults of the sea urchin species Lytechinus variegatus and Echinometra lucunter were obtained from the field for inductions and tests with their gametes in the laboratory. The species L. variegatus was used in maintenance experiments to assess health after induction (longline outdoor and indoor tanks) and mortality rates after induction by potassium chloride (KCl) and a mixture of potassium chloride with calcium chloride (CaCl2 ), and to evaluate bacterial growth as well as antibiograms of seawater resulting from induced spawning and in vitro fertilization. For the species E. lucunter, experiments with the same chemical inducers on mortality rates were carried out, as well as the conservation of oocytes in artificial seawater with antibiotics selected for their efficiency and toxicity for later use. Maintenance in the laboratory tanks, filled with seawater in a closed system, showed the lowest mortality rates in the group of non-induced organisms (control). The mixture of KCl and CaCl2 resulted in the lowest mortality rates of the adult organisms after spawning induction. The antibiotics Chloramphenicol and Gentamicin showed moderate efficiency in inhibiting bacterial growth, but with low toxicity, demonstrating the ability to maintain the integrity of sea urchin oocytes for up to 14 days under refrigeration.